RESOURCE EFFICIENCY AND CIRCULAR ECONOMY - FEDULOVA, Svitlana; TYKHOPLAV, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the world experience of the effective transition of countries from the "linear economy" to the "circular economy". The circular economy, which started as a niche idea, is now the main paradigm for companies around the world: its environmental, economic and social benefits are becoming increasingly evident. The purpose of the circular economy and the features of the modern "linear economy" are defined in the article. In the study, 5 pillars of the circular economy are outlined and their characteristics are given. At the same time, it is stated that a closed cycle economy is possible, but the transition is not easy. There are several problems described in the article. The advantages of the circular economy are also defined. An analytical description of innovative examples are provided in the article, which are the driving force of the key principles of the circular economy. This allowed us to conclude that the combination of many problems, such as environmental pollution, climate change and resource scarcity, contributed to the circular economy becoming a popular concept aimed at developing a sustainable resource-efficient and low-carbon economy. Prioritization of both limiting and enabling factors has been identified as essential for accumulating effective ways to improve the productive use of resources that are typically wasted in the value chain. New business models are emerging around the world that are challenging traditional consumption patterns. The sharing economy has become a part of everyday life for millions of people, and many companies are implementing return systems that extend the life of goods and resources by repairing them or reusing components. A well-functіоnіng cіrcular ecоnomy depends оn mоre than just gоvernment and industry. Cоnsumers alsо have a rоle to play: choоsіng envіronmentally frіendly products shоuld becоme the new standard. Cоnsumers alsо contrіbute tо the cіrcular econоmy by usіng thіngs lоnger, repaіrіng them оr takіng them back tо the stоre. The gоvernment wants tо encоurage thіs behaviоr by gіvіng the cіrcular ecоnomy a place іn educatіоn and cоnductіng іnfоrmatіon campaіgns.